2021
DOI: 10.1088/1402-4896/abeba1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible light photocatalytic properties of Fe2O3-doped carbon nitride-based organo-catalysts

Abstract: Fe2O3/g-CN heterojunction composites were successfully fabricated by a simple calcinations method using iron chloride and urea as precursors. A specific amount of Fe2O3 was incorporated on the surface of g-CN and calcinated at 400, 450, and 500 °C to obtain series of Fe2O3/g-CN (400(1), 450(2), 500(3) °C) composites. Characterization techniques were applied to measure the optical activities of Fe/CNx composites. The Fe/CN(2) sample showed a significant enhancement in the separation of photo-generated carriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…versus the irradiation time t) of the dye has been determined from the absorption spectra, where C and C o are the current and initial concentrations of the dye. Analysis of the photo-degradation shows that it obeys the first order reaction equation in the first two hours [31][32][33]:…”
Section: Photocatalytic Activity Of Zno Thin Filmsmentioning
confidence: 99%
“…versus the irradiation time t) of the dye has been determined from the absorption spectra, where C and C o are the current and initial concentrations of the dye. Analysis of the photo-degradation shows that it obeys the first order reaction equation in the first two hours [31][32][33]:…”
Section: Photocatalytic Activity Of Zno Thin Filmsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] However, g-C 3 N 4 has a low specific surface area, which limits its visible light responsivity, and the high recombination rate of electron-hole pairs results in low photocatalytic activity. [15][16][17][18] In order to address these challenges, various solutions have been attempted, including element doping, 19,20) structural defects, 21) the formation of interfacial heterojunction between the materials, [22][23][24] and the incorporation of co-catalysts. 25,26) In particular, we have confirmed that the introduction of platinum as a co-catalyst is an extremely effective method.…”
Section: Introductionmentioning
confidence: 99%